The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4319/lo.2014.59.4.1181
|View full text |Cite
|
Sign up to set email alerts
|

Application of stable isotope mixing models for defining trophic biomagnification pathways of mercury and selenium

Abstract: Trophic models based on nitrogen stable isotope ratios (d 15 N) have been shown to predict changes in mercury (Hg) concentrations in fish; however, they are usually applied at the ecosystem scale and are rarely directed at known trophic pathways. We discuss a novel approach in which we combined gut contents analysis and stable isotope analyses (d 15 N and d 13 C) into a Bayesian isotopic mixing model to provide a quantitative estimate of Hg and selenium (Se) biomagnification in an estuarine food web. Estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Variations in stable isotope ratios of 13 C/ 12 C (δ 13 C) and 15 N/ 14 N (δ 15 N) have been used extensively to examine food sources, trophic structure, and energy transfer and efficiency in lakes Rasmussen 1999, 2001;Post 2002), reservoirs (Saito et al 2001), and marine systems (Das et al 2003). In addition, interest in the sources and trophic transfer of contaminants in aquatic systems has led to studies in which δ 15 N and (or) δ 13 C values were coupled with measurements of total metal concentrations in both freshwater and marine biota (e.g., Power et al 2002;Das et al 2003;Quinn et al 2003;Larsson et al 2007;Jardine et al 2009Jardine et al , 2012Senn et al 2010;Jones et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in stable isotope ratios of 13 C/ 12 C (δ 13 C) and 15 N/ 14 N (δ 15 N) have been used extensively to examine food sources, trophic structure, and energy transfer and efficiency in lakes Rasmussen 1999, 2001;Post 2002), reservoirs (Saito et al 2001), and marine systems (Das et al 2003). In addition, interest in the sources and trophic transfer of contaminants in aquatic systems has led to studies in which δ 15 N and (or) δ 13 C values were coupled with measurements of total metal concentrations in both freshwater and marine biota (e.g., Power et al 2002;Das et al 2003;Quinn et al 2003;Larsson et al 2007;Jardine et al 2009Jardine et al , 2012Senn et al 2010;Jones et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A stable nitrogen isotope was used to document the biomagnification pathway of mercury and selenium occurs in fish (Jones et al 2014). Results indicated that mercury but not selenium was taken up by fish feeding upon the animals from the local area.…”
Section: Bioaccumulation and Biomagnificationmentioning
confidence: 99%